Integrative analysis of motor neuron and microglial transcriptomes from SOD1(G93A) mice models uncover potential drug treatments for ALS - ARĞA, KAZIM YALÇIN (My University, 2022)
Amyotrophic lateral sclerosis (ALS) is a fatal disease of motor neurons that mainly affects the motor cortex, brainstem, and spinal cord. Under disease conditions, microglia could possess two distinct profiles, M1 (toxic) and M2 (protective), with the M2 profile observed at disease onset. SOD1 (superoxide dismutase 1) gene mutations account for up to 20% of familial ALS cases. Comparative gene expression differences in M2-protective (early) stage SOD1(G93A) microglia and age-matched SOD1(G93A) motor neurons are poorly understood. We evaluated the differential gene expression profiles in SOD1(G93A) microglia and SOD1(G93A) motor neurons utilizing publicly available transcriptomics data and bioinformatics analyses, constructed biomolecular networks around them, and identified gene clusters as potential drug targets. Following a drug repositioning strategy, 5 small compounds (belinostat, auranofin, BRD-K78930611, AZD-8055, and COT-10b) were repositioned as potential ALS therapeutic candidates that mimic the protective state of microglia and reverse the toxic state of motor neurons. We anticipate that this study will provide new insights into the ALS pathophysiology linking the M2 state of microglia and drug repositioning.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Yaşam Bilimleri (LIFE); NEUROSCIENCES; Sinirbilim ve Davranış; BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); NEUROSCIENCE & BEHAVIOR; İlaç Keşfi; Duyusal Sistemler; Gelişimsel Sinirbilim; Bilişsel Sinirbilim; Hücresel ve Moleküler Sinirbilim; Sinirbilim (çeşitli); Genel Sinirbilim; İnsan Bilgisayar Etkileşimi; Yapısal Biyoloji; Moleküler Biyoloji; Klinik Biyokimya; Kanser Araştırmaları; Biyokimya; Yaşlanma; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genel Biyokimya, Genetik ve Moleküler Biyoloji; Fizik Bilimleri; Drug Discovery; Sensory Systems; Developmental Neuroscience; Cognitive Neuroscience; Cellular and Molecular Neuroscience; Neuroscience (miscellaneous); General Neuroscience; Human-Computer Interaction; Structural Biology; Molecular Biology; Clinical Biochemistry; Cancer Research; Biochemistry; Aging; Biochemistry, Genetics and Molecular Biology (miscellaneous); General Biochemistry, Genetics and Molecular Biology; Physical Sciences; SOD1 mutation; Amyotrophic lateral sclerosis; Transcriptomic; Drug repositioning; Repositioned therapeutics; AMYOTROPHIC-LATERAL-SCLEROSIS; MOUSE MODEL; IN-VITRO; CYTOTOXIC SECRETIONS; DISEASE PROGRESSION; PARKINSONS-DISEASE; INCREASES SURVIVAL; SPINAL-CORD; AURORA-B; EXPRESSION